Factors Required for Activation of Urease as a Virulence Determinant in Cryptococcus neoformans - Arpita Singh (American Society for Microbiology, 2013)
ABSTRACT Urease in Cryptococcus neoformans plays an important role in fungal dissemination to the brain and causing meningoencephalitis. Although urea is not required for synthesis of apourease encoded by URE1, the available nitrogen source affected the expression of URE1 as well as the level of the enzyme activity. Activation of the apoenzyme requires three accessory proteins, Ure4, Ure6, and Ure7, which are homologs of the bacterial urease accessory proteins UreD, UreF, and UreG, respectively. A yeast two-hybrid assay showed positive interaction of Ure1 with the three accessory proteins encoded by URE4, URE6, and URE7. Metalloproteomic analysis of cryptococcal lysates using inductively coupled plasma mass spectrometry (ICP-MS) and a biochemical assay of urease activity showed that, as in many other organisms, urease is a metallocentric enzyme that requires nickel transported by Nic1 for its catalytic activity. The Ure7 accessory protein (bacterial UreG homolog) binds nickel likely via its conserved histidine-rich domain and appears to be responsible for the incorporation of Ni2+ into the apourease. Although the cryptococcal genome lacks the bacterial UreE homolog, Ure7 appears to combine the functions of bacterial UreE and UreG, thus making this pathogen more similar to that seen with the plant system. Brain invasion by the ure1, ure7, and nic1 mutant strains that lack urease activity was significantly less effective in a mouse model. This indicated that an activated urease and not the Ure1 protein was responsible for enhancement of brain invasion and that the factors required for urease activation in C. neoformans resemble those of plants more than those of bacteria. IMPORTANCE Cryptococcus neoformans is the major fungal agent of meningoencephalitis in humans. Although urease is an important factor for cryptococcal brain invasion, the enzyme activation system has not been studied. We show that urease is a nickel-requiring enzyme whose activity level is influenced by the type of available nitrogen source. C. neoformans contains all the bacterial urease accessory protein homologs and nickel transporters except UreE, a nickel chaperone. Cryptococcal Ure7 (a homolog of UreG) apparently functions as both the bacterial UreG and UreE in activating the Ure1 apoenzyme. The cryptococcal urease accessory proteins Ure4, Ure6, and Ure7 interacted with Ure1 in a yeast two-hybrid assay, and deletion of any one of these not only inactivated the enzyme but also reduced the efficacy of brain invasion. This is the first study showing a holistic picture of urease in fungi, clarifying that urease activity, and not Ure1 protein, contributes to pathogenesis in C. neoformans